PENGARUH KOMPENSASI DAN LINGKUNGAN KERJA TERHADAP KEPUASAN KERJA KARYAWAN PT. TOR GANDA MEDAN - Fauzi Fauzi (JRMB (Jurnal Riset Manajemen & Bisnis), 2018)
This paper is based on the research regarding investigation on compensation, working environment and employees’ satisfaction in the company. In this regard, the researcher chose the employees of PT. Tor Ganda Medan as participants. The PT. Tor Ganda Medan was a company engaged in oil palm plantations and processing factory and was located on Jl. Abdullah Lubis No. 26 Medan. It was interesting to explore the effect of compensation and working environment to the employees’ satisfaction. The research type was descriptive quantitative or explanatory description in which questionnaire, interview and document used as instruments in data collection. The Likert scale used for analyzing data gained from questionnaire, while the data from interview and documents stood as complement and would be crossed-check with the questionnaire data. Statistical analysis used for this quantitative research such as multiple regressions where the population of the study consisted of 268 persons with 160 sampels through Slovin technical formula. The result of the research indicated that some problems occured in the PT. Tor Ganda Medan related to employees’ perception for unfair compensation and uncomfortable work environment that was in turn effecting to employees’ dissatisfaction and leading them to resign. The hypothesis showed that compensation and working environment simultaneously and partially has a significant effect on job satisfaction. R Square of 90.3% job satisfaction variable could be explained by the compensation variable and work environment, while the rest was 9.7% which could be explained by other factors that were not examined such as leadership style, improper placement with the expertise, the severity of the work, the nature of workers, etc. Hence, the partial results of the study showed that there was a significant effect on the job satisfaction where thecompensation was the most dominant factor influencing job satisfaction.